Efficacy of chloropyriphos as protectant of wood against borer and termite attack - Remadevi O K; Raja Muthukrishnan (Wood News, 1997)
Rubberwood [Hevea brasiliensis] stakes were treated with different concentrations of 2 different commercial formulations of chlorpyrifos, by either vacuum impregnation or dipping. Even at low concentrations the formulations were effective at preventing damage by termites (Isoptera) and powder post beetles (bostrychids and lyctids) in test yards in India when compared with untreated controls.
Keywords: Rubberwood; Wood treatment